Maternal HIV infection drives altered placental Mtb-specific antibody transfer - Nziza, Nadege; Jung, Wonyeong; Mendu, Maanasa; Chen, Tina; McNamara, Ryan P.; Fortune, Sarah M.; Franken, Kees L. M. C.; Ottenhoff, Tom H. M.; Bryson, Bryan; Ngonzi, Joseph; Bebell, Lisa M.; Alter, Galit (Frontiers in Microbiology, 2023)
Placental transfer of maternal antibodies is essential for neonatal immunity over the first months of life. In the setting of maternal HIV infection, HIV-exposed uninfected (HEU) infants are at higher risk of developing severe infections, including active tuberculosis (TB). Given our emerging appreciation for the potential role of antibodies in the control of Mycobacterium tuberculosis (Mtb), the bacteria that causes TB, here we aimed to determine whether maternal HIV status altered the quality of Mtb-specific placental antibody transfer. Antigen-specific antibody systems serology was performed to comprehensively characterize the Mtb-specific humoral immune response in maternal and umbilical cord blood from HIV infected and uninfected pregnant people in Uganda. Significant differences were noted in overall antibody profiles in HIV positive and negative maternal plasma, resulting in heterogeneous transfer of Mtb-specific antibodies. Altered antibody transfer in HIV infected dyads was associated with impaired binding to IgG Fc-receptors, which was directly linked to HIV viral loads and CD4 counts. These results highlight the importance of maternal HIV status on antibody transfer, providing clues related to alterations in transferred maternal immunity that may render HEU infants more vulnerable to TB than their HIV-unexposed peers.